Psychoacoustic investigation of listening with quadrophonic earphones - ŁĘTOWSKI, Tomasz; MAKOWSKI, Wojciech (Archives of Acoustics, 1980)
Despite the existence of a variety of designs of quadrophonic earphones, there have been no papers concerned with the psychoacoustic phenomena accompanying quadrophonic earphone projection. The present paper presents the results of seven experiments in the field of the psychoacoustics of hearing under conditions of earphone projection involving the use of four transducers, and also presents the technical principles of the formation of binaural images. The results obtained permit the conclusion to be drawn that quadrophonic or even stereophonic earphone projection involving four transducers enables the sound sources to be located outside the listener's head. It seems interesting that the listening to stereophonic signals with four transducers gives effects incomparably better than those for the projection with two transducers and is of a quality comparable with the monitoring of quadrophonic signals.